THE INFLUENCE OF DIGITAL TRANSFORMATION, EDUCATION, AND INNOVATION ON VISITOR SATISFACTION AT THE SULTAN SULAIMAN BADRUL ALAMSYAH MUSEUM IN TANJUNGPINANG CITY WITH SERVICE QUALITY AS AN INTERVENING VARIABLE - Eka Febryanti; Angelina E. Rumengan; I Wayan Catrayasa (CV. RADJA PUBLIKA, 2025)
This research aims to analyze the influence of digital transformation, education, and innovation on visitor satisfaction at the Sultan Sulaiman Badrul Alamsyah Museum in Tanjungpinang, with service quality as an intervening variable. The study adopts a quantitative approach using Structural Equation Modeling (SEM) with Partial Least Squares (PLS) analysis to test the relationships among the variables. Data were collected through questionnaires distributed to museum visitors, focusing on their perceptions of digital service implementation, educational programs, innovative initiatives, service quality, and overall satisfaction. The results indicate that digital transformation, education, and innovation have a positive and significant effect on visitor satisfaction, both directly and indirectly through service quality. Furthermore, service quality serves as a critical mediating factor that strengthens the impact of these variables on visitor satisfaction. The findings suggest that improving digital features, educational activities, and innovative services, supported by consistent quality standards, can significantly enhance the visitor experience and satisfaction. This research provides practical implications for museum management in adopting digital strategies and educational innovations to improve public engagement and competitiveness in the cultural tourism sector.